Recent Advances in Poultry Nutrition and Production - Morgan, Natalie; Attia, Youssef A. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The aim of this Special Issue was to publish high-quality papers on poultry nutrition and the inter-relations between nutrition, metabolism, gut microflora, and poultry performance. Therefore, we present here original research articles in the following topics:- the nutrient requirements of poultry;- the impact of dietary fibre on poultry health and performance;- the use of feed additives to improve gut microflora and performance;- the effect of feeding on poultry meat and egg quality;- factors that cause variation in feed ingredients used in poultry diets;- alternative feed ingredients for use in poultry feed formulations;- the impact of gastrointestinal pH on nutrient bioavailability and the intestinal microbiota in poultry;- phytate and xylan 'susceptibility' in relation to the effects of enzymes;- factors that influence reactivity and enzyme efficacy;- in vitro models to determine the digestibility of poultry diets.